Respon Pertumbuhan dan Produksi Tanaman Mentimun (Cucumis sativus L.) Terhadap Pemberian Pupuk Npk dan Kompos Ampas Tebu - Ziraluo, Trinitas; Panggabean, Ellen L. (Universitas Medan Area, 2025)
This study aims to examine the effect of NPK fertilizer application, bagasse compost, and its interaction on the growth and production of cucumber plants (Cucumis sativus L.) of the Zafaty F1 variety. The research was carried out using a factorial Group Random Design (RAK) with two factors, namely the dose of NPK fertilizer (1, 2, and 3 tons/ha) and bagasse compost (0, 10, 20, and 30 tons/ha). The observed parameters included plant height, stem diameter, flowering age, fruit diameter, number of fruits per sample and per plot, and fruit weight per sample and per plot. The results of the analysis showed that NPK fertilizer had a very real effect on the acceleration of flowering life, while bagasse compost had a real effect on the number of fruits per sample and per plot in the second harvest. However, no significant effect of either treatment was found on vegetative growth (stem height and diameter) as well as fruit size and weight. These findings indicate that NPK fertilization and bagasse compost have not been optimal in increasing overall cucumber production. Further research is needed to explore more precise dosage and sustainable application strategies to maximise crop yields.